KAJIAN KUALITAS PELAYANAN UNIT AIRPORT OPERATION CONTROL CENTER DI BANDAR UDARA SULTAN AJI MUHAMMAD SULAIMAN SEPINGGAN - M. Budi Kuntjoro; Sunarno; Imam Sarwo Aji (Politeknik Penerbangan Indonesia Curug, 2018)
Indonesian Civil Aviation Institute Curug Tangerang have a new aviation engineering building. In this study author discusses the reliability of the existing electrical installation network in the new aviation engineering building which is useful to see the reliability of the electrical installation security in new aviation engineering building. The current condition of existing installation in the aviation engineering building is assumed new as the aviation engineering building is completed in 2016. So the installation in this building has not been known wheter it is safe during the teaching and learning process of cadets. Then in case of excessive current the safety may not be able to hold it like MCB, MCCB, cable and grounding. So here author will assess whether the reliability of the existing electrical installation in the new aviation engi